Micro Incision Cataract Surgery (MICS)/ Bimanual Phacoemuslsification. Initial Problems and the Solutions - Shoaib, Khawaja Khalid (Pakistan Journal of Ophthalmology, 2009)
Purpose: To describe the difficulties faced by a phacoemulsification (phaco) surgeon switching to Micro incision cataract surgery (MICS) - bimanual phaco so that others are better prepared when starting the procedure. Material and Method: Initial fifty cases of MICS -bimanual phaco were analyzed to find out the problems encountered peculiar to the new procedure. All the complications that occur during the conventional co-axial phaco were excluded. Operation time of twenty cases of MICS was compared to operation time of twenty cases of coaxial phaco in various categories of cataract hardness. Average effective phaco time (EPT) of grade 2 cataract for MICS and coaxial phaco were compared. Results: Spray of liquid emitting through wound, anterior chamber (A/C) collapse, increased operation time, increased size of irrigating chopper causing difficulty in manipulation and its sharpness resulting in rupture of posterior capsule, were encountered. Operation times of MICS were greater than coaxial group from 3.12 to 8.04 minutes for various categories of cataract hardness. EPT of grade 2 cataract for MICS was 3.92±2.07sec and coaxial phaco was 5.67±3.7sec. It means more operation time but less phaco for MICS as compared to coaxial phaco. Conclusion: In spite of enormous advantages of MICS - bimanual phaco, it has some problems which are unique to the procedure and phaco surgeon should be ready to face them.